The modifications in surgical technique and its impact on short term morbidity in modified radical mastectomy: a tertiary care hospital experience - Bandyopadhyay, Arnab; Talwar, Rajnish; Patel, Amol; Jaiswal, Pradeep (International Surgery Journal, 2019)
Background: Necrosis of flap margins, postoperative pain and shoulder dysfunction are amongst the main concerns of the breast surgeon performing modified radical mastectomy (MRM). This pilot study is aimed to evaluate the effects of these procedural modifications and whether should it be included as a standard practice. Methods: A total of 150 MRM patients are evaluated in this single arm cohort study in a tertiary care centre over a time period of 2 years (2014-2016). The following modifications are adopted in the usual procedure of the MRM: double skin incision and elective excision of the skin margins, injecting long acting local anesthetic agent (bupivacaine) preoperatively around the nerve pedicles in axilla and postoperative positioning of arm in hyper abduction and early resumption of Shoulder exercises Results: Flap margin necrosis has reduced considerably (2.6%) in comparison to historical data (15%). Pain relief was significantly less on first post-operative day (mean VAS score 2.93) which encouraged early shoulder mobilisation. Flap necrosis was more in T4 tumours (75% vs 25%) which was significant with a p value of .004. Similarly flap necrosis at 48hrs was more with the patients who received neoadjuvant chemotherapy (NACT) with a p value of 0.047. Higher nodal burden was significantly correlated with flap necrosis with a p value of .002. Conclusions: This pilot study provides preliminary evidence of the positive effects of the proposed modifications on minimising morbidity following MRM further convincing evidence by way of multi-centric randomized control trials, will be required to validate the conclusions of this study.